Neurofascin and Compact Myelin Antigen-Specific T Cell Response Pattern in Chronic Inflammatory Demyelinating Polyneuropathy Subtypes - Diederich, Jan-Markus; Staudt, Maximilian; Meisel, Christian; Hahn, Katrin; Meinl, Edgar; Meisel, Andreas; Klehmet, Juliane (Frontiers in Neurology, 2018)
ABSTRACT Objective: To investigate whether chronic inflammatory demyelinating polyneuropathy (CIDP) and its subtypes differ in their type 1 T-helper (TH1) cell response against nodal/paranodal neurofascin (NF186, NF155) as well as myelin protein zero (P0 180-199) and myelin basic protein (MBP 82-100). Methods: Interferon-γ (IFN-γ) ELISPOT assay was used to detect antigen-specific T cell responses in 48 patients suffering typical CIDP (n=18), distal acquired demyelinating polyneuropathy (DADS; n=8), multifocal acquired demyelinating sensory and motor polyneuropathy (MADSAM; n=9), and sensory CIDP (n=13) compared to other polyneuropathies (ON; n=19) and healthy controls (HC; n=9). Results: Compared to controls, MADSAM and sensory CIDP patients showed broadest IFN-γ T cell responses to all four antigens. Positive IFN-γ responses against two or more antigens were highly predictive for CIDP (positive predictive value; PPV = 0.95) and were found in 77% of CIDP patients. Patients with limited antigen-specific response were females, more severely affected with neuropathic pain and proximal paresis. The area under the ROC curve (AUC) of NF186 in MADSAM was 0.94 (95% CI 0.82-1.00) compared to ON. For sensory CIDP, AUC of P0 180-199 was 0.94 (95% CI 0.86-1.00) and for MBP 82-100 0.95 (95% CI 0.88-1.00) compared to ON. Conclusion: Cell-mediated immune responses to (para)nodal and myelin-derived antigens are common in CIDP. TH1 response against NF186 may be used as a biomarker for MADSAM and TH1 responses against P0 180-199 and MBP 82-100 as biomarkers for sensory CIDP. Larger multi-center studies study are warranted in order to establish these immunological markers as a diagnostic tools.